Optimization of E-Commerce Sales System using User-Centered Design at Pepito Kudus - Saidun Basyar, Aminun Fais; Arifin, Muhammad; Fithri, Diana Laily (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
E-commerce refers to the process of buying and selling products or services digitally via an internet connection, encompassing transactions, payments, and online deliveries. Pepito Kudus is a retail clothing business located in Kudus City. However, the store still operates using a traditional sales system and has not yet adopted an e-commerce platform. Transactions are manually recorded in physical ledgers, while customers from outside the city place orders via Facebook or WhatsApp chat, requiring store employees to send multiple product photos to potential buyers. This manual approach presents several challenges, particularly in terms of efficiency, as the purchasing process takes longer. To address these issues, Pepito Kudus requires an online sales system to facilitate more effective and efficient digital transactions. The User-Centered Design (UCD) method is applied in system development, ensuring that the design prioritizes user needs and undergoes comprehensive testing to optimize usability and user experience. The implementation of this system is expected to streamline the sales process, enable more efficient transactions, accelerate data processing, enhance sales accuracy, and provide customers with a more convenient ordering experience.